2006
DOI: 10.1038/nrm1907
|View full text |Cite
|
Sign up to set email alerts
|

The multifaceted mismatch-repair system

Abstract: By removing biosynthetic errors from newly synthesized DNA, mismatch repair (MMR) improves the fidelity of DNA replication by several orders of magnitude. Loss of MMR brings about a mutator phenotype, which causes a predisposition to cancer. But MMR status also affects meiotic and mitotic recombination, DNA-damage signalling, apoptosis and cell-type-specific processes such as class-switch recombination, somatic hypermutation and triplet-repeat expansion. This article reviews our current understanding of this m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
1,060
1
13

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 1,162 publications
(1,121 citation statements)
references
References 114 publications
22
1,060
1
13
Order By: Relevance
“…1 and discussion below), and reconstitutions in the Li and Modrich laboratories of MMR reactions from purified proteins possess many of the key features associated with MMR in vivo (Constantin et al, 2005;Dzantiev et al, 2004;Zhang et al, 2005). These studies were predicated on a large body of earlier work that identified individual components from active fractions of cell extracts and characterized partial reactions (reviewed in Jiricny, 2006). Zhang et al (2005) have demonstrated MMR of a G-T mismatch in 5′-directed repair reactions containing MutSα, MutLα, RPA, EXO1, PCNA, RFC, HMGB1, DNA polymerase δ, and DNA ligase I (Yuan et al, 2004).…”
Section: Mutation Avoidance and Post-replication Repairmentioning
confidence: 99%
See 4 more Smart Citations
“…1 and discussion below), and reconstitutions in the Li and Modrich laboratories of MMR reactions from purified proteins possess many of the key features associated with MMR in vivo (Constantin et al, 2005;Dzantiev et al, 2004;Zhang et al, 2005). These studies were predicated on a large body of earlier work that identified individual components from active fractions of cell extracts and characterized partial reactions (reviewed in Jiricny, 2006). Zhang et al (2005) have demonstrated MMR of a G-T mismatch in 5′-directed repair reactions containing MutSα, MutLα, RPA, EXO1, PCNA, RFC, HMGB1, DNA polymerase δ, and DNA ligase I (Yuan et al, 2004).…”
Section: Mutation Avoidance and Post-replication Repairmentioning
confidence: 99%
“…Since discrimination between mismatched DNA and perfectly paired DNA is not large, most commonly no more than two orders of magnitude (reviewed in Jiricny, 2006;Kunkel and Erie, 2005;Schofield and Hsieh, 2003), the issue of finding a mismatch is not trivial. Total internal reflection fluorescence microscopy of yMSH2-MSH6 reveals that the protein travels along undamaged DNA duplexes via ID diffusion (Gorman et al, 2007).…”
Section: Mutation Avoidance and Post-replication Repairmentioning
confidence: 99%
See 3 more Smart Citations